A financial stress indicator for Germany - Norbert Metiu (Deutsche Bundesbank, 2024)
This paper describes the Bundesbank's weekly financial stress indicator for Germany. The indicator condenses several financial market variables into a summary measure of financial stress. It represents a contemporaneous, market-based indicator that captures the materialisation of systemic risk along three different risk dimensions - credit, liquidity and market risk. Judged by this measure, the German financial system has experienced its most severe financial stress period since 2002 during the 2008 global financial crisis, with highly elevated levels in all three dimensions of financial stress. The indicator also points to historically high stress levels during the euro area sovereign debt crisis in the early 2010s. Recent readings of the indicator, by contrast, indicate historically low levels of financial stress.
Keywords: E44; E51; G12; G17; 330; diffusion index; factor model; financial conditions; financial stability